Electrical Textile: Graphite Paste on Gloves for Touching Screen of Smartphones and Tablets - Ristiana, Qintar Alifah (Bumi Publikasi Nusantara, 2022)
Wearing personal protective equipment is a must during the covid-19 pandemic when you have to go outside the house. The covid-19 pandemic makes shopping, work, studying, and other activities run at home. With advances in technology, touch screen gloves for smartphones and tablets are a solution so that online service sellers and people who have to leave the house are protected and easily use their smartphones. The purpose of this paper is to prove that the use of graphite media can be used for touch screens on gloves in the use of smartphones and tablets. The population of this research is chemical substances which are conductor, thickener, and binder. The sample used by researchers was graphite as a conductor, alginate as a thickener, and polyacrylate as a binder. The method used is an experimental method and literature review, an experimental method using certain tools and materials in this experiment. The experimental results show that graphite paste can make gloves as a conductor and gloves with polyacrylate has a washing resistance of 10-50 times household washing. The graphite paste is a conductor for making gloves that can touch smartphones and tablets screens also polyacrylate as a binder can make washing resistance. So it can be concluded that graphite can be used for touch screens on gloves in the use of smartphones and tablets and has a washing resistance.